HR2U in the eyes of the beholder / Al-amin Abdul Razi - Abdul Razi, Al-amin (Universiti Teknologi MARA, Perak, 2021)
28 September 2021 - The Administration Off ice of UiTM Perak branch has organized an online knowledgesharing titles' HR2U Dari Lensa Warga UiTM Cawangan Perak' using the Webex application. Thepurpose of the program is to provide the step-by-step hands on training of the HR processes in the HR2Usystem. The HR processes that was discussed are the Confirmation Into Services screen, Staff Leavescreen, Time Management System screen, Application for Going Abroad screen and Integrity screen.